2012
DOI: 10.1038/tp.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: do all roads lead to dopamine or is this where they start? Evidence from two epidemiologically informed developmental rodent models

Abstract: The idea that there is some sort of abnormality in dopamine (DA) signalling is one of the more enduring hypotheses in schizophrenia research. Opinion leaders have published recent perspectives on the aetiology of this disorder with provocative titles such as ‘Risk factors for schizophrenia—all roads lead to dopamine' or ‘The dopamine hypothesis of schizophrenia—the final common pathway'. Perhaps, the other most enduring idea about schizophrenia is that it is a neurodevelopmental disorder. Those of us that mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 131 publications
7
64
0
Order By: Relevance
“…These findings strongly suggest that 1,25(OH) 2 D 3 is a direct differentiation agent for dopaminergic neurons. Schizophrenia is regarded as a neurodevelopmental disease and alterations in the early ontogeny of dopamine systems have been proposed to be a central etiological feature of the disease (Eyles et al, 2012). The direct modulation of TH by 1,25(OH) 2 D 3 as demonstrated here might help us to better understand the etiology for the epidemiological link between DVD-deficiency and schizophrenia.…”
Section: Resultsmentioning
confidence: 87%
“…These findings strongly suggest that 1,25(OH) 2 D 3 is a direct differentiation agent for dopaminergic neurons. Schizophrenia is regarded as a neurodevelopmental disease and alterations in the early ontogeny of dopamine systems have been proposed to be a central etiological feature of the disease (Eyles et al, 2012). The direct modulation of TH by 1,25(OH) 2 D 3 as demonstrated here might help us to better understand the etiology for the epidemiological link between DVD-deficiency and schizophrenia.…”
Section: Resultsmentioning
confidence: 87%
“…Although no animal model can replicate all aspects of the complexities of human neuropsychiatric disorders such as schizophrenia, these can be deconstructed into more simplified endophenotypes that embody the major symptom domains (van den Buuse 2010; Eyles et al 2012). For example, schizophrenia is characterized by: positive symptoms, including hallucinations and delusions; negative symptoms, including social withdrawal, and anhedonia; and cognitive impairments.…”
Section: Animal Models Of Schizophreniamentioning
confidence: 98%
“…Meyer et al (2007) suggested that immunological activation at different times of prenatal development may have distinct neurodevelopmental consequences. Maternal infections in late pregnancy may especially affect late neurodevelopmental programs in the developing fetus, thereby inducing a more restricted pathological phenotype in the grown offspring, or spare the emergence of postnatal brain and behavioral pathology (Meyer et al, 2006), such as schizophrenia (Eyles et al, 2012;Meyer et al, 2011) and attentional impairments (Vuillermot et al, 2012).…”
Section: Introductionmentioning
confidence: 99%